Pengaruh Produksi Beras, Harga Beras dan Konsumsi Beras Terhadap Impor Beras di Provinsi Sumatera Utara Tahun 2009-2019 - Lily Syafitri Batubara; Noni Rozaini (Universitas 17 Agustus 1945 Semarang, 2023)
The purpose of this study is to see how changes in rice imports in North Sumatra Province between 2009 and 2019 are due to changes in rice production, prices and consumption. To see how the influence of independent factors on the dependent variable, this study uses multiple linear regression analysis. The results of multiple linear regression analysis partially show that domestic rice imports in North Sumatra are negatively and not significantly affected by rice production. In North Sumatra, the price of rice is positively and insignificantly affected by rice production, while rice consumption is negatively affected and may not be significantly affected by rice imports. There is no visible effect between the variables of rice production, rice prices, rice consumption, and rice from 2009 to 2019.